The Influence of Service Marketing Mix on Word of Mouth in Using Halal Kitchen Hotels - Hayeemad, Mahmood; Graisutrang, Adam (WMS Journal of Management, 2020)
This research aims to study the impacts among service marketing mix, satisfaction, customer loyalty, and word of mount upon using the Halal kitchen hotels. The data were collected from 400 Muslim Thai and foreign tourists in Krabi using purposive sampling with a set of questionnaires and analyzed by employing Structural Equation Modeling (SEM). The results of the SEM analysis showed that the service marketing mix had an influence on the customer satisfaction (β =.81, P < .001) and loyalty (β =.65, P < .001). Customer satisfaction had an effect on customer loyalty (β =.30, P < .001). However, customer satisfaction did not have an impact on word of mouth communication (β =.01). Customer loyalty had the influence on word of mouth communication (β =.90, P < .001). Variance (R2) of customer satisfaction, loyalty and word of mouth communication variables were .66, .84 and .90, respectively. The results contribute to a growing body of knowledge and enhance an understanding of a marketing process in a form of word of mount communication in using the Halal kitchen hotels.